First study on the immunohistochemical expression of cyclooxygenase-2 and clinicopathological association in canine hepatoid gland neoplasms - Pinkarn Chantawong; Thanongsak Mamom; Sahatchai Tangtrongsup; Setthakit Chitsanoor; Hassadin Boonsriroj (Veterinary World, 2022)
Background and Aim: Hepatoid gland neoplasms (HGNs) constitute one of the most common cutaneous tumors that arise from perianal glands in dogs and are clinically characterized by rapid growth. Cyclooxygenase-2 (COX-2), the inducible form of the enzyme, is associated with several hallmarks of tumorigenesis. Its expression has been confirmed in several human and animal neoplastic tissues, but there are no reports in hepatoid gland tissues. Therefore, this study aimed to investigate COX-2 immunoexpression in canine HGNs, compare the expression among groups of normal hepatoid glands, hepatoid gland adenomas (HGAs), hepatoid gland epitheliomas (HGEs), and hepatoid gland carcinomas (HGCs), and assess the association of the COX-2 expression with clinicopathological features.